Inhaled mRNA therapy for treatment of cystic fibrosis: Interim results of a randomized, double‐blind, placebo‐controlled phase 1/2 clinical study - Rowe, S.M.; Zuckerman, J.B.; Dorgan, D.; Lascano, J.; McCoy, K.; Jain, M.; Schechter, M.S.; Lommatzsch, S.; Indihar, V.; Lechtzin, N.; McBennett, K.; Callison, C.; et al. (Journal of cystic fibrosis, 2023)
•CFTR mRNA was delivered by aerosol in lipid nanoparticles to cystic fibrosis adults.•In this small first-in-human study treatment was generally safe and well tolerated.•Quickly resolving fever and hypersensitivity reactions were noted in some subjects.•Lung function remained stable after treatment but no benefit was observed. MRT5005, a codon-optimized CFTR mRNA, delivered by aerosol in lipid nanoparticles, was designed as a genotype-agnostic treatment for CF lung disease. This was a randomized, double-blind, placebo-controlled Phase 1/2 study performed in the US. Adults with 2 severe class I and/or II CFTR mutations and baseline ppFEV1 values between 50 and 90% were randomized 3:1 (MRT5005: placebo). Six dose levels of MRT5005 (4, 8, 12, 16, 20, and 24 mg) or placebo (0.9% Sodium Chloride) were administered by nebulization. The single ascending dose cohort was treated over a range from 8 to 24 mg; the multiple ascending dose cohort received five weekly doses (range 8–20 mg); and the daily dosing cohort received five daily doses (4 mg). A total of 42 subjects were assigned to MRT5005 [31] or placebo [11]. A total of 14 febrile reactions were observed in 10 MRT5005-treated participants, which were mild [3] or moderate [11] in severity; two subjects discontinued related to these events. Additionally, two MRT5005-treated patients experienced hypersensitivity reactions, which were managed conservatively. The most common treatment emergent adverse events were cough and headache. No consistent effects on FEV1 were noted. MRT5005 was generally safe and well tolerated through 28 days of follow-up after the last dose, though febrile and hypersensitivity reactions were noted. The majority of these reactions resolved within 1–2 days with supportive care allowing continued treatment with MRT5005 and careful monitoring. In this small first-in-human study, FEV1 remained stable after treatment, but no beneficial effects on FEV1 were observed.